The Truth-Telling of Truth-Seekers: Evidence from Online Experiments with Scientists - Moritz A. Drupp; Menusch Khadjavi; Rudi Voss (Center for Economic Studies and ifo Institute (CESifo), 2024)
Academic honesty is crucial for scientific advancement, yet replication crises and misconduct scandals are omnipresent. We provide evidence on scientists' truth-telling from two incentivized coin-tossing experiments with more than 1,300 scientists. Experiment I, with predominantly European and North-American scientists, shows that fewer scientists over-report winning tosses when their professional identity is salient. The global Experiment II yields heterogeneous effects. We replicate Experiment I's effect for North-American scientists, but find the opposite for Southern European and East-Asian scientists. Over-reporting correlates with publication metrics and country-level measures of academic and field-experimental dishonesty, suggesting that country-level honesty norms also guide truth-telling by scientists.
Keywords: C93; D82; K42; J45; 330; truth-telling; lying; identity; science; cross-country; experiment